METHODOLOGY FOR IMPLEMENTING INCLUSIVE EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (American Journal of Pedagogical and Educational Research, 2025)
Inclusive education is a critical approach that promotes equal opportunities for all children, including those with disabilities or special needs, to learn and participate in educational settings. This scientific article discusses the methodology for effectively implementing inclusive education in preschool educational organizations. The article highlights the importance of creating a supportive and inclusive environment, fostering collaboration among educators, families, and specialists, and providing individualized support to meet the diverse needs of all children. Various strategies and best practices for incorporating inclusive education in preschool settings are explored, emphasizing the significance of early intervention and personalized learning experiences. By following a comprehensive methodology, preschools can ensure that every child receives the necessary support and resources for optimal development and learning outcomes.